Regulation of Transcription Elongation by the XPG-TFIIH Complex Is Implicated in Cockayne Syndrome - Narita, Takashi (Mol Cell Biol, 2015)
XPG is a causative gene underlying the photosensitive disorder xeroderma pigmentosum group G (XP-G) and is involved in nucleotide excision repair. Here, we show that XPG knockdown represses epidermal growth factor (EGF)-induced FOS transcription at the level of transcription elongation with little effect on EGF signal transduction. XPG interacted with transcription elongation factors in concert with TFIIH, suggesting that the XPG-TFIIH complex serves as a transcription elongation factor. The XPG-TFIIH complex was recruited to promoter and coding regions of both EGF-induced (FOS) and housekeeping (EEF1A1) genes. Further, EGF-induced recruitment of RNA polymerase II and TFIIH to FOS was reduced by XPG knockdown. Importantly, EGF-induced FOS transcription was markedly lower in XP-G/Cockayne syndrome (CS) cells expressing truncated XPG than in control cells expressing wild-type (WT) XPG, with less significant decreases in XP-G cells with XPG nuclease domain mutations. In corroboration of this finding, both WT XPG and a missense XPG mutant from an XP-G patient were recruited to FOS upon EGF stimulation, but an XPG mutant mimicking a C-terminal truncation from an XP-G/CS patient was not. These results suggest that the XPG-TFIIH complex is involved in transcription elongation and that defects in this association may partly account for Cockayne syndrome in XP-G/CS patients.